Peran Masyarakat Lokal dalam Pengembangan Pariwisata - Hartadji, Diandra Khansa (Jurnal Abdimas Pariwisata, 2024)
The Role of Local Communities in Tourism Development Tourism has experienced development in recent years and contributes to national economic growth. But apart from that, tourism also has an impact on social and cultural aspects. Local communities have an important role in tourism development, because they have specific knowledge and experience about the local culture and environment. Thus, this article aims to illustrate the important role of local communities in tourism development, as well as how they can contribute to economic and socio-cultural growth in areas where tourism develops. The method used in this article is literature review. The result is that local communities have a role in increasing the success of tourism destinations, such as their involvement in resource ownership and management, sustainable development, providing tourist experiences, empowering the local economy, preserving culture, and welcoming tourists.